Google Drive Based Digital Archives: Implementation Review in Curriculum Management - Siti Mufidatunrofiah; Binti Syafaati Maysyaroh; Suratman Suratman (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
The massive development of technology underlies the demands for digitization. One crucial effort of digitization in the field of education is the use of digital archives in the management of educational institutions. This research aims to describe the implementation of Google Drive-based digital archives focusing on curriculum management in MTs Al-Mahsyar Nurul Iman Tenggarong Seberang. A qualitative method with a descriptive type is employed in conducting this research. Data related to the digital management of curriculum archives are obtained through interviews, observations, and documentation. The results of this research indicate that the digital management of curriculum archives based on Google Drive at MTs Al-Mahsyar Nurul Iman Tenggarong Seberang has been implemented, although the curriculum archives are not yet fully efficiently managed. The implementation of Google Drive as a curriculum field archive medium is evident in efforts involving the creation, storage, control, distribution, utilization, and supervision of archives, with subject archive classifications including madrasah work meetings, learning materials, implementation reports, evaluation and student learning outcome reports, student graduation administration, as well as EMIS (Education Management Information System) data.